Performance analysis of elite female water polo teams in the 2013 World Championships - Enomoto, I.; Kobayashi, D.; Suga, M.; Minami, T. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
This study compares the performance characteristics of the high- and low-ranking teams in the female water polo tournament at the 2013 FINA World Championships. Data on 2,500 shots and 682 exclusion fouls were obtained from official score sheets, which were provided by the organising committee of the FINA World Championships. Performance variables were defined as follows: number of shots and goals by style (center, action, 5-m, counter-attack, exclusion, or penalty), shot results (goal scored or goal saved by goalkeeper [GK)), exclusion fouls (in field or in center}, goal percentages, and percentage of GK saves for each style of shot. The frequency of the performance variables, both in offense and defense, were calculated per match. The sixteen participating teams were divided into four groups based on their final ran kings in the championships as follows: 1st- to 4th-place teams Gl, 5th- to 8th-place teams G2, 9th- to 12th-place teams (G3), and 13th- to 16thplace teams (G4}. In terms of offense, Gl had significantly higher frequencies, compared to the other groups, of counter-attack shots and counter-attack goals. G4 had significantly lower frequencies, compared to the other groups, of total shots and action goals. As for defense characteristics, Gl showed significantly lower frequencies of action shots, total shots, and GK saves in counter attacks. G4 showed significantly higher frequencies of counter-attack shots, action goals, center goals, and GK saves.